AB1024 Side effects associated with the use of zolendronic acid. (23rd January 2014) - Lopez, L.M.; Cacheda, A.P.; Salman-Monte, T.C.; Padrò, I.; Ciria, M.; Blanch-Rubiό, J.
Abstract : Background: The zolendronic acid (ZO) is indicated in the treatment of osteoporosis and Paget's disease, as well as in the prevention of fractures. The adverse effect (AE) more prevalent is the flu-like syndrome 1-2 (fever, myalgia, headache, arthralgia) that occurs early after the infusion. Some studies have detected an increased number of arrhythmias (atrial fibrillation) in patients treated with ZO 3 . Likewise, there have been reports ofosteonecrosis of the jaw 4, especially in cancer patients receiving high doses of the drug. It may also be related to atypical femoral fractures, attributed to a suppression of bone metabolism ("frozen bone"). Other AE are slight impairment of renal function, uveitis 5 and hypocalcemia 6 . Objectives: To determine the prevalence of adverse effects after the administration of zoledronate in a number of patients of our unit. Methods: Retrospective, descriptive study of patients treated with zoledronate from 01/01/2006 to 01/01/2011. Demographic and clinical characteristics, as well as type of side effects, were analyzed. Results: 775 patients corresponding to a total of 1653 infusions of zoledronic acid with different indications were reported. There were 582 (75%) women and 193 (25%) men. The mean age was 68 (±12) years. 511 (66%) patients received ZO for senile osteoporosis, 165 (21%) patients for Corticosteroid -Induced Osteoporosis, and 96 (12%) patients for the treatment of Paget's disease. In our cohort the prevalence of all AE was 4.9%. The main AE described were: flu-like syndrome in 32 patients (4%), osteonecrosis of the jaw in two patients (0.25%) and uveitis in two patients (0.25%). Bilateral atypical diaphysis fracture was objectified in 1 patient (0.12%). Reasons for treatment cessation were: medical indications in 34 patients (4.3%), side effects in 6 patients (0.75%) and ineffectiveness in 1 patient. Conclusions: The use of zoledronic acid is safe in our study. The most frequent AE was the flu-like syndrome with a lower prevalence than in other series 1 . The reason could be that we collected only the cases that alarmed the patients. As in other series (4, 5, 6), the prevalence of the rest of AE described (osteonecrosis of the jaw, uveitis, atypical diaphysis fractures) was very low. No cases of renal toxicity, symptomatic arrhythmias, or hypocalcemia were found. References: BlackDM, Boonen S, Cauley J, Delmas P, Eastell R, Reid I, Rosario- Jansen T, Caminis J, Zhang J, Hu H, Cummings S 2006 Effect of once-yearly infusion of zoledronic acid 5 mg on spine and hip fracture reduction in postmenopausal women with osteoporosis: the HORIZONpivotal fracture trial. J Bone Miner Res 21(Suppl 1):S16 (Abstract) Adami S, Bhalla AK, Dorizzi R, 1987 The acute-phase response after bisphosphonate administration. Calcif Tissue Int 41: 326-331. Cummings SR, Schwartz AV, Black DM. Alendronate and atrial fibrillation. N End J Med. 2007;356:1895–6. Khosla S, Burr D, Cauley J, Dempster DW, Ebeling PR, Felsenberg D, et al. Bisphosphonate-associated osteonecrosis of the jaw: report of a task force of the American Society for Bone and Mineral Research. J Bone Min Res. 2007;22:1479–91. Muñoz OrtegoJ, Carbonell AbelloJ.Oculartoxicity, bisphosphonate and Paget disease. MedClin(Barc).2009;133:198. 27. Arboleya L, Alperi M, Alonso S. Efectos adversos de los bisfosfonatos. Reumatol Clin. 2011. doi:10.1016/j.reuma.2010.10.005 Disclosure of Interest: None Declared